ASSESSMENT OF THE INVESTMENT ATTRACTIVENESS OF NATIVE COPPER FORMATION OF THE VOLYN ORE REGION - MYKHAILOV, Volodymyr; ANDREEVA, Olena; SYDORCHUK, Vitalii (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Background. Copper is one of the critical metals for the industry of Ukraine. More than 150 copper ore occurrences of various genetic types on the territory of Ukraine are known. One of the most interesting is the occurrences of native copper formation in the Riphean trappean formations of the Volyn copper ore district. To determine the degree of investment attractiveness of copper ore occurrences, an objective assessment of the resource base of the copper ore district is necessary. Methods. The analysis of the results of prospecting and economic assessment within the ore occurrences of the Volyn copper ore region were conducted: data on wells were reviewed, promising intervals were selected, areas were specified and copper ore resources were recalculated.Results. A recalculation of the resource potential of the Volyn copper ore region for three metallogenic areas: Volynsk, Kuhotsk-Volsk and Manevytsk was carried out. It was shown that their previous economic assessment during the exploration and assessment studies was overestimated by an order of magnitude. Сonclusions. It has been established that native copper mineralization of the Volyn copper ore region has not significant investment attractiveness and further development of its potential by future investors is associated with significant risks. The group of occurrences of the western border of the Hirnytsk horst (Zhyrychi, Zalysy-Shmenky) is of some interest, but the insignificant parameters of the ore bodies, their wide scattering over the area and across the section, the low copper content and the need for an underground method of mining call into question the economic feasibility of their development.